PERLINDUNGAN HUKUM KONSUMEN DALAM JUAL BELI MOBIL BEKAS MELALUI PLATORM ONLINE - Muhamad Nur Halim; Indah Sari (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
The rapid advancement of information technology has impacted many sectors of life, including the buying and selling of goods and services. One recent trend is online used car transactions, which offer convenience, time efficiency, and wider access to vehicles without the need to visit a showroom in person. However, these online transactions also pose various potential legal issues, such as inaccurate vehicle information, hidden defects, and minimal transparency regarding vehicle origins. This study aims to examine legal protection for consumers in these transactions, based on the legal framework in Indonesia, specifically Law No. 8 of 1999 concerning Consumer Protection. Furthermore, the responsibilities of business actors and alternative dispute resolution options available to consumers are discussed. The method used is a normative juridical approach by examining regulations, literature, and case studies. The results of the study indicate the need for regulatory updates and increased legal literacy and oversight of digital platforms to provide maximum protection to consumers.